Informal Sector Economy, Child Labor and Economic Growth in Developing Economies: Exploring the Interlinkages - Shahid, Sumbal; Khan, Rana Ejaz Ali (Asian Development Policy Review, 2020)
The study explores the interlinkages among informal sector, child labor and economic growth covering 50 developing economies for the time period 2001-2015 through 3SLS approach. The results show that informal sector positively influences child labor and child labor positively influences informal sector. It creates a vicious cycle of underdevelopment and poverty. Similarly child labor positively contributes in economic growth and economic growth enhances child labor in developing economies. However, informal sector increases economic growth but economic growth decreases informal sector. So there emerged a complex and discoursing interlinkage among informal sector, child labor and economic growth in developing economies. The informal sector is positively influenced by population growth. Child labor is also positively influenced by population growth and age dependency but negatively by globalization. Economic growth is positively influenced by capital formation, globalization and governance. A multidimensional approach is required for decreasing the size of informal sector economy and eliminating the child labor along with having good economic growth. Control of population growth is emerged one of them which may slide down informal sector economy and child labor. The capital formation and governance may be a part of the policy framework for economic growth.